Increased symmetrical dimethylarginine in ischemic acute kidney injury as a causative factor of renal L-arginine deficiency - Betz, Boris; Möller-Ehrlich, Kerstin; Kress, Tobias; Kniepert, Joachim; Schwedhelm, Edzard; Böger, Rainer H.; Wanner, Christoph; Sauvant, Christoph; Schneider, Reinhard (Translational research : the journal of laboratory and clinical medicine, 2013)
Availability of L-arginine, the exclusive substrate for nitric oxide synthases, plays an important role in kidney ischemia/reperfusion injury. The endogenous L-arginine derivatives asymmetrical dimethylarginine (ADMA) and symmetrical dimethylarginine (SDMA) block cellular L-arginine uptake competitively, thereby inhibiting the production of nitric oxide. ADMA also blocks nitric oxide synthase activity directly. Here, we investigate the pathomechanistic impact of ADMA and SDMA on ischemic acute kidney injury. Rats were subject to bilateral renal ischemia (60 minutes)/reperfusion (24 hours) injury. Impairment of renal function was determined with inulin clearance (glomerular filtration rate) and para-aminohippurate (PAH) clearance (renal plasma flow). L-arginine, ADMA, and SDMA levels were measured by liquid chromatography–tandem mass spectrometry. L-arginine was extracted from renal tissue and analyzed by enzyme-linked immunosorbent assay, and protein and messenger RNA expressions were determined by Western blot and real-time reverse transcription polymerase chain reaction. Renal function deteriorated severely after ischemia/reperfusion injury, as demonstrated by inulin and PAH clearance. Serum ADMA and SDMA increased, but tissue expression of specific ADMA or SDMA synthesizing and metabolizing enzymes (protein arginine methyltransferases and dimethyl arginine dimethylaminohydrolases) did not alter. Serum L-arginine increased as well, whereas intracellular L-arginine concentration diminished. Renal messenger RNA expression of cationic amino acid transporters, which mediate L-arginine uptake, remained unchanged. In serum, the ratio of L-arginine to ADMA did not alter after ischemia/reperfusion injury, whereas the ratios of L-arginine to SDMA and ADMA to SDMA decreased. A marked increase in serum SDMA, especially when accompanied by a diminished L-arginine-to-SDMA ratio, might reflect competitive inhibition of cellular L-arginine uptake by SDMA. As a consequence, a pathologic renal L-arginine deficiency in ischemic acute kidney injury results.